PENGAMBILAN MINERAL ELEKTROLIT DARI LIMBAH GARAM - Hapsari, Nur Hapsari (Jurnal Teknik Kimia, 2008)
Bittern is a thick liquid that obtained from crystallization waste that left from salt making process.Bittern contain many minerals including macro mineral micro mineral. This mineral formed because ittakes part in crystallization at salt making process. From the great quantities that bittern contain, theresome minerals that have high that is: Magnesium (Mg), Natrium (Na), Kalium (K), and Calcium (Ca).These four minerals important minerals that needed for human body’s health, so that can be used asmineral ionic supplement that have benefit for human’s health.Electro dialysis membrane is one of ions separation process from some liquid with the use of highelectrical wave through semi permeable membrane that have permeable characteristic for some specificions. This process produce one part that we call“Konsentrat” and the other part we call it “Diluat” . The variable that we are going to use for this research is : bittern concentrations, voltage and timeof operation. And the best research result take place in condition : feed concentration in bittern 1composition, voltage that we used is 2,9 volt and time of operation is 150 minutes and also produce %magnesium (Mg) rejection = 91,9%, % Natrium (Na) rejection = 74,66%, % (K) Kalium rejection =92,88% and % Calcium (Ca) rejection = 96,19%.Key words : bittern, membrane, electro dialysis, concentrate, diluat, rejection